2001
DOI: 10.4049/jimmunol.167.7.3919
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Kupffer Cell-Derived IL-10 for Host Defense in Septic Peritonitis

Abstract: Intra-abdominal infection in patients following major visceral surgery is associated with high mortality. Using a macrophage depletion technique, we demonstrate that in murine septic peritonitis, Kupffer cells are a major source of systemic IL-10 levels. Kupffer cell-depleted mice were highly susceptible to the lethal effects of septic peritonitis and exhibited an increased bacterial load. Kupffer cell-depleted mice were protected by the administration of an IL-10-Fc fusion protein. Loss of Kupffer cell-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 59 publications
4
57
2
2
Order By: Relevance
“…Interestingly, the massive increase in IL-10 observed in STAT-1 -/-mice appears to be confined to circulating blood cells, and not tissue macrophages. Previous work documents Kupffer cells as important in LPS-stimulated IL-10 production [13], but our results suggest that blood monocytes circulating through the organs are responsible for IL-10 production during an acute systemic release of LPS. The different experimental systems employed in these studies likely explain the contrasting results, and more work will need to be done to better understand why cells in different stages of differentiation appear to differentially respond to a simulated systemic gram-negative infection.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, the massive increase in IL-10 observed in STAT-1 -/-mice appears to be confined to circulating blood cells, and not tissue macrophages. Previous work documents Kupffer cells as important in LPS-stimulated IL-10 production [13], but our results suggest that blood monocytes circulating through the organs are responsible for IL-10 production during an acute systemic release of LPS. The different experimental systems employed in these studies likely explain the contrasting results, and more work will need to be done to better understand why cells in different stages of differentiation appear to differentially respond to a simulated systemic gram-negative infection.…”
Section: Discussioncontrasting
confidence: 79%
“…In vitro, IL-10 is produced by monocytes and macrophages following exposure to LPS [9], and its mechanism of action includes down-regulating the production of pro-inflammatory cytokines such as IFN-c, as well as repressing IFN-c-mediated signal transducer and activator of transcription (STAT)-1 activation through induction of the suppressor of cytokine signaling family of proteins [12]. The importance of IL-10 in controlling proinflammatory cytokine release is evidenced by studies demonstrating increased mortality among mice with neutralized or deficient IL-10 following LPS challenge [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it appears conceivable that, during septic peritonitis, endothelial cells contribute to systemic IL-6 and CXCL1 levels, whereas IL-10 and IL-12p40 may be released into the circulation by myeloid cells. Consistent with this notion, previous work showed that hepatic Kupffer cells are the major source of systemic IL-10 in murine septic peritonitis (12), and Kupffer cell density was found to be comparable among WT, Myd88 LSL/LSL , and Myd88 MYEL mice (Supplemental Fig. 1E).…”
Section: Myd88 Expression In Both Myeloid and Nonmyeloid Cells Is Reqsupporting
confidence: 70%
“…In addition, high systemic IL-10 levels in CCR2 antibody-treated mice may also contribute to IL-10 levels at local sites like peritoneal cavity. Previous work has shown that systemic IL-10 levels in the CASP model of septic peritonitis are mostly derived from hepatic Kupffer cells [41], suggesting that this major population of tissue macrophages may also be involved in the effects of CCR2 blockade.…”
Section: Discussionmentioning
confidence: 99%